The Failure of Investment Strategy to Earn Outperform Investment Return on Equity Mutual Funds in ASEAN Market (A Study to Improve Performance Evaluation Model and to Enhance Implementation of Investment Strategy) - Tito Edwin Hasudungan Hutabarat; Poltak Sinaga; John Tampil Purba; Anton Wachidin Widjaja (Budapest International Research and Critics University, 2022)
Traditional approach in implementation of investment strategy in managing equity mutual funds is no longer enough to earn outperform return in the volatile market. This research proposed empirical evidences that none of equity mutual funds were traded in ASEAN market during period January 2015 to December 2020 could continuously earn outperform return. This because the implementation of the determined strategy, whether active investment strategy or passive investment strategy, without significant stock selection ability and market timing ability. This research proposes to enhance the methodology of implementation of the determined investment strategy by implementing significant stock selection ability and market timing ability. Furthermore, a continuous monitoring on the market condition, fund performance as well as performances of the underlying assets are necessary to do especially if the changes in all of these variables may change the investment risks therefore certain action shall be taken not only to avoid investment loss but more importantly is to earn outperform return.